Critical discourse analysis on BTS commencement speech in dear class of 2020 - Ni Putu Mutia Amandari; I Made Netra; Ni Made Suwari (Journal of Education, Social & Communication Studies, 2024)
The aim of the study is to examine the representative of critic in CDA and the hidden meaning in BTS Commencement Speech in Dear Class of 2020. The analysis of this research based on theory of CDA and its analysis methods which were represented by Van Dijk. Whereas the discussion used descriptive qualitative research method which deals with data that are in the form of word, rather than statistics and attempts to arrive at a rich description of something systematically. It starts by analyzing the represented critic on the text and separated them into an expression from each data. Then, it is continued by analyzing the hidden meaning of the text. Since it is a critical discourse, therefore those features are analyzed critically. The result shows that CDA can explore the relationships among language, power, ando ideology. Through the language used, it can be known the strength of power and the purpose of the speaker, which the power is strongly felt and the ideology is clearly seen as well as understandable.